2010
DOI: 10.2215/cjn.06580909
|View full text |Cite
|
Sign up to set email alerts
|

Low Risk for Nephrogenic Systemic Fibrosis in Nondialysis Patients Who Have Chronic Kidney Disease and Are Investigated with Gadolinium-Enhanced Magnetic Resonance Imaging

Abstract: Background and objectives: During the past decade, nephrogenic systemic fibrosis (NSF) has been reported in patients who have severe renal impairment and have been exposed to a gadolinium (Gd)-based contrast agent during magnetic resonance imaging (MRI). As a result of positive reporting bias, many suitable patients with chronic kidney disease (CKD) are being denied a highly important form of investigation that can be safely undertaken. We analyzed the safety of Gd-MRI in patients with CKD and varying levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 22 publications
3
50
0
Order By: Relevance
“…With the more stable salts of Gadolinium (MultiHance), no cases of NSF have been reported in 784 ESRD patients at our institution (29,30). A larger study from the United Kingdom showed no cases of NSF in 2053 patients with CKD (608 patients had CKD stages 4 and 5) who received Gadolinium (31).…”
Section: Renal Complicationsmentioning
confidence: 77%
“…With the more stable salts of Gadolinium (MultiHance), no cases of NSF have been reported in 784 ESRD patients at our institution (29,30). A larger study from the United Kingdom showed no cases of NSF in 2053 patients with CKD (608 patients had CKD stages 4 and 5) who received Gadolinium (31).…”
Section: Renal Complicationsmentioning
confidence: 77%
“…In general, gadoliniumenhanced MRI is used as a standard for diagnostic imaging 1) . Since gadolinium enhancement in this case was relatively contraindicated due to the unstable renal function (s -Cre, 1.1 -1.4 mg/dL ; eGFR, 29 -36 mL/min/1.73 m²), use of MRI and Ga scintigraphy allowed successful diagnosis 36) . In this case, swelling in the falx cerebri was not detected on MRI at the time of sinusitis (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The risk of nephrogenic systemic fibrosis, however, is low, even in patients with chronic kidney disease. 24,25 Even so, it is recommended that in patients with moderate-to-end stage kidney disease, imaging methods other than MR angiography with a gadoliniumbased contrast agent should be selected whenever possible. 24 Answers to question 7 (32 responded).…”
Section: Methodsmentioning
confidence: 99%